Where do Smallholder Farmers get Their Information? An Exploration of the Sources of Agricultural Information in Northwest Cambodia. - Presley Nickens; David Ader; Jean Pierre Enriquez; Ricky Bates; Tom Gill; Sovanneary Huot; Lyda Hok; Srean Pao (Journal of International Agricultural and Extension Education, 2023)
A significant emphasis on scaling up food security efforts is needed to achieve Sustainable Development Goal 2 (Zero Hunger) by 2030. Scaling up sustainable intensification efforts for Cambodian smallholder farmers is key since they face greater exposure to the uncertainties of climate change, globalizing markets, and rural-to-urban migration. One way to increase the effectiveness of efforts and the scaling up of sustainable intensification technologies is through improving access to information about production and marketing technologies. This study aimed to identify sources of information about sustainable technologies available to smallholders and barriers that may be preventing adoption. Information was gathered from a household survey to document the sources of agricultural information for smallholders in Northwest Cambodia. This research suggests Cambodian smallholders are receiving agricultural extension services, however, the overall quality and effectiveness of these messages are unknown, since NGOs with competing foci are the primary provider of extension information. Smallholders face significant barriers that prevent the adoption of sustainable technologies and participation in markets, such as low price for goods, poor product quality, lack of time, and concerns for safety. Future endeavors to strengthen the price of goods and alleviate market-related challenges would likely result in increased smallholder income and food availability.
Keywords: extension; sustainable intensification; agriculture information; smallholder; technology